Machado de Assis, jornalista: o homem, o texto, o tempo. - Granja, Lucia [UNESP] (My University, 2010)
This article analyses some of Machado de Assis’ newspaper chronicles written in 1878 for O Cruzeiro. We intend to show that behind their extremely free literary composition, those texts show the author’s deepest critical point of views. Respecting the narrator fictional status, we are trying to see, as carefully as this subject demands on us, the man behind the journalist.

Este artigo analisa algumas das crônicas que Machado de Assis escreveu, em 1878, para O Cruzeiro, e mostra como, por detrás da liberdade de composição literária desses textos, encontramos a visão de mundo de um cronista profundamente crítico. Sem desrespeitar o estatuto ficcional que ocupa o narradorcronista, procuramos enxergar, tão cuidadosamente quanto requer a sutileza do assunto, o homem por detrás do cronista, na experiência jornalística de 1878.
Keywords: Machado de Assis; Machado de Assis - crônica; Biografia; Journalism; Literature; Machado de Assis; Newspaper Chronicles; Reader